Tourist Information Center (TIC) Application for Department of Tourism – East Kalimantan - Dhanita Almira; Eny Maria; Annafi Franz (TEPIAN, 2023)
- The activities of tourism information centers in Department of Tourism of East Kalimantan have not been exposed, which are still manually using brochure sheets, YouTube or Instagram to develop tourism in various fields in order to boost regional income from various potentials they have. Information systems are needed in order to produce the right and clear information in order to help tourists or tourists in their trips. The Tourist Information Center application in East Kalimantan Province is an idea that is expected to provide solutions to solve these problems. By using two methods of data collection, namely the interview and observation methods at agencies. The construction of the system used in this study uses the System Development Life Cycle (SDLC) with a waterfall model or called a waterfall, which is started by the stage of literature study, problem analysis, design (design), system implementation and testing. With the Tourist Information Center application, it can be used as a reference for tourists to vacation in East Kalimantan and provide information about tourism or lodging in East Kalimantan.